Automação residencial microcontrolada via plataforma arduino - Dezulinski, Gabriel (2014)
The Residential Automation or Domotics every day is gaining popularity, but still the cost is high. Several studies on the subject have been made for the creation of new technologies and equipment, so thinking this regard the work provides a study and application of a model home automation. The system works basically connecting equipment existing in a home, such as alarm systems, electronic gates, lighting microcontrolled systems on a platform that is connected to a processing unit via a USB cable. Serial communication with the user of the system can control the equipment from your home through various devices such as tablets, mobile phones and computers. To access the system via mobile devices was used internet shield module that consists of a plate connected to Arduino platform by establishing a medium to connect to the Ethernet network with the assistance of the W5100 library developed by company Serial Link, it was possible provide the platform arduino programming in HTML (Hyper Text Markup Language) and an IP address which is used by devices to connect to the network via Ethernet platform. The prototype was implemented with a graphical user interface developed with the help of software LabVIEW 2012. This in turn is responsible for managing information between the Arduino platform and graphical interface, using the LabView was possible to create a graphical screen with various icons, each of which when clicked executes a function in the microcontroller, that is, we light a lamp or even open an electronic gate through a simple click on a button at the screen. Another feature of the system is the ability to execute predefined functions, such as determining when we would like the alarm system was turned on, other functions can be programmed according to the user's needs.